2022
DOI: 10.1021/jacs.2c04976
|View full text |Cite
|
Sign up to set email alerts
|

Bright, Modular, and Switchable Near-Infrared II Emission from Compact Tetrathiafulvalene-Based Diradicaloid Complexes

Abstract: Near-infrared (NIR)-emitting molecules are promising candidates for biological sensing and imaging applications; however, many NIR dyes are large conjugated systems which frequently have issues with stability, solubility, and tunability. Here, we report a novel class of compact and tunable fluorescent diradicaloid complexes which are air-, water-, light-, and temperature-stable. These properties arise from a compressed π manifold which promotes an intense ligand-centered π–π transition in the NIR II (1000–1700… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 64 publications
1
42
0
Order By: Relevance
“…To resolve any trends in the biradical character and triplet–singlet (T–S) gaps of bimetallic TTFtt 2– bridged complexes, we investigate the electronic structures of a series of complexes that have been recently reported (Pt, PtCF3, Pd, Ni, Sn, Fe), as well as the newly proposed and yet to be experimentally characterized PtCOD. These compounds are of particular interest in the development of optically addressable molecular qubits or switches, and a recent experimental and computational investigation by the authors has shown them to exhibit fluorescent behavior driven by a π* → π transition of the TTFtt ligand . The chemical structures of all investigated compounds are displayed in Figure .…”
Section: Discussion and Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To resolve any trends in the biradical character and triplet–singlet (T–S) gaps of bimetallic TTFtt 2– bridged complexes, we investigate the electronic structures of a series of complexes that have been recently reported (Pt, PtCF3, Pd, Ni, Sn, Fe), as well as the newly proposed and yet to be experimentally characterized PtCOD. These compounds are of particular interest in the development of optically addressable molecular qubits or switches, and a recent experimental and computational investigation by the authors has shown them to exhibit fluorescent behavior driven by a π* → π transition of the TTFtt ligand . The chemical structures of all investigated compounds are displayed in Figure .…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…First, broken symmetry (BS) DFT geometry optimizations were performed with the B3LYP functional in combination with the LANL2DZ basis set for Pt, Pd, Sn and the 6-31G* basis set for all remaining atoms, relaxing the geometry from the one obtained in the solid state via single crystal X-ray diffraction (XRD). ,, The use of unrestricted Kohn–Sham DFT calculations, allowing them to break the spin-symmetry, is essential for the accurate capture of the geometry and properties of systems displaying multireference character. , The DFT optimizations were followed by high-level CASSCF and NEVPT2 calculations allowing us to capture accurately the effects arising from both the multireference and biradical character and dynamic correlation. A minimal active space comprising four electrons distributed in four spatial orbitals, [4,4], was chosen for the CASSCF calculations as the strong correlation in these systems has been shown to be limited to two frontier natural orbitals, largely comprised of TTFtt-based π orbitals that give rise to the biradical character.…”
Section: Discussion and Resultsmentioning
confidence: 99%
See 3 more Smart Citations